Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Multikultural - Firmansyah Firmansyah (Universitas Negeri Medan, 2020)
The curriculum is an instrument to run an education system to be more targeted in accordance with what is aspired in national education. The development of community life that is very dynamic and can even happen quickly requires the development of the curriculum must also be able to adjust to the development of this social life. Indonesia is known as a multicultural country that consists of diverse tribes and religions that inhabit this region. The diversity of cultural patterns in ethnicity and religion can certainly be a trigger for friction between each of these groups. To overcome this, the world of education in facing this challenge needs to think about how curriculum development that leads to harmony that responds to this multicultural situation. Curriculum development cannot be separated from several instruments, namely the objective component, affective domain, and psychomotor domain. Likewise in the multicultural-based Islamic religious education curriculum which must also refer to these domains despite having the goal of helping to create a life that is tolerant of the multicultural life of Indonesian people. The research method used in this research is the literature study method by examining several literature studies in the form of books, journals, archives and other documentation about the curriculum which can then be analyzed for inclusion in multicultural-based Islamic religious education curriculum development.